Serial Interval Distribution of COVID-19 among Iranian Reported Confirmed Cases - Zare , Fariba; Emamian , Mohammad Hassan; Chaman , Reza; Rohani-Rasaf , Marzieh; Goli , Shahrbanoo; Talebi , Solmaz; Hosseinzadeh , Ali; Khosravi , Ahmad (Shahroud Journal of Medical Sciences, 2021)
Type of manuscript: short reportIntroduction: Serial interval refers to the average time between of the onset of the symptoms of two successive cases. Serial interval distribution can be used for the calculation of the basic reproduction number (R0), transmission rate, and study of an epidemic trend. This study aims to investigate the mean, standard deviation, and distribution of serial interval among the confirmed cases of COVID-19 using a Gamma distribution. Methods: To determine the serial interval, 60 confirmed infected cases of COVID-19 (based on PCR test results) in February 20th-May 20th, 2020 were selected as the cases. For these cases, 37 transmissions occurred. The data of the dates of the occurrence of primary and secondary symptoms were collected by referring to the COVID-19 surveillance system and interviewing the patientsResults: The findings showed that the median and mean of the serial interval were 3.0 and 4.5± 3.5 days. The findings showed that the median of the serial interval was 3.0 days (with the inter-quartile range of 2.0-6.0). The mean serial interval was 4.5± 3.5 days (95% confidence interval: 3.1-5.5).Conclusions: Our report showed a shorter period for a serial interval less than the previous reported interval in China. It seems that regarding the shorter serial interval reported in this study, the basic reproduction numbers reported by the first papers published in Iran have been overestimated regarding the serial interval of 7.5 days.Key words: COVID-19, Serial interval, Gamma distribution